Investigations of genotoxic activity of antimicrobial/antiviral agent FS-1 in human lymphocytes and tumor cell - Nersesyan, A.; Ilin, A.; Kulmanov, M. (Цитология и генетика, 2011)
A very promising antiviral and antimicrobial agent FS-1 was studied for its ability to induce DNA damage and micronuclei in human tumor cell lines HeLa and Caco-2 at concentrations of 200, 500 and 1000 mg/ml without exogenous metabolic activation. The compound was additionally tested for DNA damaging ability in human lymphocytes at concentrations of 200, 400 and 800 mg/ml. Neither DNA damage nor micronucleus formation was observed after treatment of all types of cells with FS-1. Based on these results, FS-1 can be further studied for its safety to humans for potential application in clinical medicine as an antimicrobial/antiviral drug.